2016
DOI: 10.1002/lary.26402
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β antagonist attenuates fibrosis but not luminal narrowing in experimental tracheal stenosis

Abstract: NA. Laryngoscope, 127:561-567, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Induced myofibroblasts increase fibrotic markers, such as stress fiber, α‐smooth muscle actin (α‐SMA) and collagen . Research has shown that TGF‐β1 antagonistic antibodies represent antifibrotic activity in various experimental models of fibrosis . Therefore, TGF‐β1 is a potential therapeutic target in fibrotic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Induced myofibroblasts increase fibrotic markers, such as stress fiber, α‐smooth muscle actin (α‐SMA) and collagen . Research has shown that TGF‐β1 antagonistic antibodies represent antifibrotic activity in various experimental models of fibrosis . Therefore, TGF‐β1 is a potential therapeutic target in fibrotic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies that have developed animal models of airway stenosis have used an open approach. Authors have induced airway injury with a wide variety of methods, including brushing of the trachea, the use of the carbon‐dioxide laser, the application of silver nitrate or hydrochloric acid to the airway mucosa, and cautery . Balloon dilation is frequently used for the management of SGS; however, this modality disrupts scar tissue through radial high‐pressure force and may fracture the cricoid cartilage, depending on balloon size and pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A wide array of methods for inducing airway stenosis in animal models has been described, including intubation only, brushing, application of silver nitrate or hydrochloric acid, use of electrocautery, and use of the carbon‐dioxide laser . Previous authors have not, however, consistently assessed the postinjury endoscopic appearance of the airway, postinjury respiratory symptoms, and histologic findings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations